Peran Bimbingan Perkawinan Pranikah Terhadap Keutuhan Rumah Tangga - Rambe, Ronimah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The focus of this research is. The Role of Premarital Marriage Guidance on Household Integrity in Southeast Padangsidimpuan District, by raising two main issues, namely 1) What is the Process of Premarital Guidance for Married Couples in Southeast Padangsidimpuan District? 2) What is the Role of Premarital Marriage Guidance on Household Integrity in Southeast Padangsidimpuan District? The aim is to find out 1) the process of premarital guidance for married couples in Southeast Padangsidimpuan district 2) the role of premarital marriage guidance on household integrity in Southeast Padangsidimpuan sub-districtThis research is a Field Research study that uses data collection techniques, namely by means of: Observation, Interview, and documentation, then taking books related to this research such as Journals, Government Publications, as well as sites or other sources that support this research. The results of the research that the researchers got from the research site, the process of providing premarital marriage guidance carried out by the KUA, namely people who are about to get married must register themselves and their partners with the KUA and have completed the prescribed documents. Then the KUA will give invitations to prospective married couples to take premarital guidance for prospective bridal couples with the material of preparing a solid marriage towards a sakinah, mawaddah, warahmmah family, fiqh munakahat, (marriage, divorce, tahaharah and iddah), the rights of husband and wife obligations , and managing conflict and building family resilience. Premarital guidance materials are delivered through lecture, discussion, and question and answer methods.